Impact of information, communication technology and housing industry on financial market development. (May 2022) - Sepehrdoust, Hamid; Ahmadvand, Shokoufeh; Mirzaei, Nesa
Abstract: The economic growth and development of a country are highly dependent on the performance of the capital market and its financial system, and to have a proper financial system, the development of Information and Communication Technology (ICT) to reduce costs of transactions, as well as the proper functioning of the parallel markets such as housing sector economy is essential. The study aims to investigate the impact of the Information, Communication Technology (ICT), the housing market, and other macroeconomic variables including the inflation rate and exchange rate on the performance of the financial market to survive Iran economy, under economic sanctions and political crises during the years 1994–2020. For this purpose, Autoregressive Distributed Lag (ARDL) method is used to estimate the research model and analyze the collected data. The results show that ICT and the inflation rate had positive effects, while the housing market development and the exchange rate had negative effects on the performance of the stock exchange financial market during the years of economic sanctions and political crises. Highlights: The imposition of economic sanctions on Iran oil export, and banning banking transactions lead the economy to political crisis. During the recession, the stock market played an effective role in collecting savings, and providing sources of income to deal with the government budget deficit. The housing market as a competitive parallel market has a negative and significant effect on the stock exchange's performance. ICT infrastructures and online trading systems have positive consequences such as speeding up trading, and faster transfer of funds electronically.